2010
DOI: 10.1177/0886109909354979
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Harassment Experiences and Their Psychological Correlates Among a Diverse Sample of College Women

Abstract: This study explored the relationship between sexual victimization and psychological outcomes in two samples of a total of 410 college women in two southern states, as well as racial differences in the prevalence of and responses to sexual harassment experiences. It found an alarmingly high rate of sexual victimization among both the Black and the White students. Internalized shame was a useful construct for understanding the relationship between sexual harassment and potential psychological correlates. The fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 31 publications
2
30
0
1
Order By: Relevance
“…The relation between harassment and health outcomes is likely to be more complex given individuals’ personality characteristics, coping styles, family history of alcoholism or mental health, and race to name a few. In fact, some research has found race differences in prevalence of and reaction to different types of SH (Yoon, Funk, & Kropf, 2010; Kearney & Gilbert, 2012). Additionally, research has shown that previous SH is one of the best predictors of future victimization.…”
Section: Discussionmentioning
confidence: 99%
“…The relation between harassment and health outcomes is likely to be more complex given individuals’ personality characteristics, coping styles, family history of alcoholism or mental health, and race to name a few. In fact, some research has found race differences in prevalence of and reaction to different types of SH (Yoon, Funk, & Kropf, 2010; Kearney & Gilbert, 2012). Additionally, research has shown that previous SH is one of the best predictors of future victimization.…”
Section: Discussionmentioning
confidence: 99%
“…Yoon, Funk, and Kropf (2010) reported on the internalized shame that victims of aggressive behavior experience. In the instance of being a victim of bullying, adolescents struggle to understand why they are singled out for harassment.…”
Section: Shame the Shame Of Victimhoodmentioning
confidence: 98%
“…While several studies have reported that women experience greater mean levels of SH than men (Berdahl and Moore, 2006; Das, 2009; Hand and Sanchez, 2000; Kalof et al, 2001; Lott et al, 1982; Reilly et al, 1986), others have reported more nuanced (McGinley et al, 2011), nonsignificant (Rospenda et al, 2000), or reversed (McMaster et al, 2002; Petersen and Hyde, 2009a,b; Wei and Chen, 2012) links between gender and SH. Still, studies have shown that some women are especially stressed or prone to self-blame by this form of victimization, which may have implications on their mental health (Goldstein et al, 2007; Lott et al, 1982; Petersen and Hyde, 2013a, 2013b; Till, 1980; Yoon et al, 2010), although few studies have attempted to understand these relations longitudinally in a young adult collegiate sample. Further, while men have overall higher rates of substance use than women (Goldstein et al, 2007; Greenbaum et al, 2005; O'Malley and Johnston, 2002), research indicates that college women have experienced a notable increase in problem drinking behaviors (e.g., binge drinking) compared to male students, whose rates have not exhibited a similar increase (Hoeppner et al, 2013; Newes-Adeyi et al, 2005).…”
Section: Examinations Of Sh Over Timementioning
confidence: 99%
“…While some studies have found that incidences of SH are higher in these groups, and particularly among minority women (Berdahl and Moore, 2006; Cortina et al, 1998; Goldstein et al, 2007; McLaughlin et al, 2012), others have shown that racial and ethnic minority status is linked to fewer reported incidences of sexual harassment, perhaps due to increased tolerance of sexually harassing behaviors (Clodfelter et al, 2010; Cortina et al, 2001; Goldstein et al, 2007; Ho et al, 2012; Kearney and Gilbert, 2012; Krieger et al, 2006; Welsh et al, 2006; Yoon et al, 2010). Further, one investigation of SH in college students showed no differences in rates of SH experiences across ethnic/racial groups (Kalof et al, 2001).…”
Section: Examinations Of Sh Over Timementioning
confidence: 99%